PERANCANGAN DATABASE SISTEM KEARSIPAN DI SMP 13 NEGERI TARAKAN MENGGUNAKAN DBLC - Syaddam, Syaddam; Febrianti, Zelda; Christian, Melky; Samuel, Helda (Universitas Muria Kudus, 2025)
Effective and efficient information management is essential in various sectors, including the educational environment. This study aims to design an archiving database system that can improve the efficiency of archive management at SMP Negeri 13 Tarakan. The method used in this study is the Database Life Cycle, which includes the stages of database planning, system definition, requirements collection and analysis, database design, and DBMS selection. The results of this study are a database system consisting of 11 main tables, namely detail_surat_masuk, surat_masuk, pelaporan_surat_masuk, referensi_kategori_surat, gtk, kontak_gtk, pelaporan_surat_keluar, surat_keluar, pihak_eksternal, pengguna, dan referensi_peran. This database system allows recording, searching, and reporting of archival data in a more systematic and organized manner. The integration of XAMPP, MySQL, and phpMyAdmin technologies provides efficiency, dynamism, and scalability advantages, thus enabling the development of responsive, adaptive, and customizable web applications to the needs of an ever-growing organization. Database design is produced through several stages. Namely, planning, needs analysis, conceptual and physical database design, and implementation using phpMyAdmin and MySQL. These design stages are carried out systematically to ensure that the database system built can support effective and efficient archive management. In addition, further development can include improving data security to keep stored information safe and accessible only to authorized parties